The subversion of the apocalypses in the Book of Jubilees - Hanneken, Todd Russell (Early Judaism and its literature, 2012)
Jubilees uses the literary genre to raise the issues typical of apocalypses--including revelation, angels and demons, judgment, and eschatology--but rejects what the apocalypses typically say about those issues, subverting reader expectations with another view.